2020
DOI: 10.1016/j.clae.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Could telehealth help eye care practitioners adapt contact lens services during the COVID-19 pandemic?

Abstract: The COVID-19 pandemic has necessitated government-imposed restrictions on social interactions and travel. For many, the guidance has led to new ways of working, most notably a shift towards working remotely. While eye care practitioners (ECPs) may continue to provide urgent or emergency eye care, in many cases the travel restrictions present a unique challenge by preventing conventional face-to-face examination. Telephone triage provides a useful starting point for establishing at-risk and emergency patients; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 57 publications
0
43
0
1
Order By: Relevance
“…Unfortunately, respondents of this study showed both behaviours (showering as well as use of tap water during lens case cleaning). Similarly, Vianya-Estopa et al Nagra et al [32] highlight that aftercare appointments had traditionally offered an ideal opportunity to assess contact lens compliance, but in the current times ECPs are encouraged to also use alternative ways (e.g. videos or patient information sheets, raising awareness of lens care phone apps).…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, respondents of this study showed both behaviours (showering as well as use of tap water during lens case cleaning). Similarly, Vianya-Estopa et al Nagra et al [32] highlight that aftercare appointments had traditionally offered an ideal opportunity to assess contact lens compliance, but in the current times ECPs are encouraged to also use alternative ways (e.g. videos or patient information sheets, raising awareness of lens care phone apps).…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
“…Daily disposables offer an advantage over reusable lenses in terms of non-compliance with cleaning and care procedures (relying on optimal handwashing only) [ [30] , [31] ]. Nagra et al [ 32 ] highlight that aftercare appointments had traditionally offered an ideal opportunity to assess contact lens compliance, but in the current times ECPs are encouraged to also use alternative ways (e.g. videos or patient information sheets, raising awareness of lens care phone apps).…”
Section: Discussionmentioning
confidence: 99%
“…However, this enterprise might be new-fangled in Jordan because of the lack of experience and legislation related to telehealth in general and teleoptometry in particular. In the UK, Nagra et al have also pointed to possible limitations of using teleoptometry by ECPs because of difficulties in the development of optometry specific evidence-based guidance for teleoptometry [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, the present results indicate that the simplicity of daily disposables offers a significant advantage as opposed to the complex steps required to achieve full compliance with reusable lenses. [18 19] However, swapping a patient to daily disposable lenses of the same stated parameters does not result in the same lens fit [32] and telemedicine is not at a stage where lens fit can be accurately assessed remotely [33], so unless the patient has worn a particular soft daily disposable contact lens before, changing during the pandemic is not a safe option. During these challenging times, practitioners have been asked to exercise their professional judgement when monitoring the care of contact lens wearers [34].…”
Section: Discussionmentioning
confidence: 99%